2023
DOI: 10.1101/2023.02.03.23285441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neurophysiological brain-fingerprint of Parkinson’s disease

Abstract: Brain-fingerprinting is a neuroimaging approach that is expanding the neuroscientific perspective on inter-individual diversity in health and disease. In the present study, we used brain-fingerprinting to advance the neurophysiological characterization of Parkinson's disease (PD). We derived the brain-fingerprints of patients with PD and age-matched healthy controls from the rhythmic and arhythmic spectral features of brief and task-free magnetoencephalography recordings. Using this approach, the individual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 129 publications
(327 reference statements)
0
3
0
Order By: Relevance
“…Substantial evidence [64][65][66] supports the role of mu-opioid and endocannabinoid systems in depression and anxiety, indicating that a shift toward decreases in activity of these systems (relative to GABAergic and glutamatergic systems) might represent a compensatory or neuroprotective effect against psychiatric symptoms in PD. Our group has also shown that the neurophysiological fingerprint of patients with PD is less distinct in regions rich in mu-opioid and cannabinoid systems, 67 indicating that the moment-to-moment variability of neurophysiology may be contributing to this finding.…”
Section: Discussionmentioning
confidence: 78%
“…Substantial evidence [64][65][66] supports the role of mu-opioid and endocannabinoid systems in depression and anxiety, indicating that a shift toward decreases in activity of these systems (relative to GABAergic and glutamatergic systems) might represent a compensatory or neuroprotective effect against psychiatric symptoms in PD. Our group has also shown that the neurophysiological fingerprint of patients with PD is less distinct in regions rich in mu-opioid and cannabinoid systems, 67 indicating that the moment-to-moment variability of neurophysiology may be contributing to this finding.…”
Section: Discussionmentioning
confidence: 78%
“…The discrepancies were particularly pronounced in the alpha band (8)(9)(10)(11)(12)(13), where MZ twins matched with an accuracy of 47.8% ([33.3, 66.7]) compared to only 1.2% for DZ twins ([0.0, 5.0]). In the beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), accuracies were 52.1% for MZ twins ([33.3, 70.0]) versus 7.1% for DZ twins ([0.0, 20.0]).…”
Section: Individual Neurophysiological Profiling and Differentiationmentioning
confidence: 99%
“…Leveraging intra-class correlation (ICC) statistics (2,3,29) (see Methods), we found that cortical activity in the theta (4-8 Hz; average ICC = 0.74), alpha (8)(9)(10)(11)(12)(13) Hz; ICC = 0.83), and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz; ICC = 0.74) frequency bands are the most distinctive traits of neurophysiological profiles between individuals (Figure 1C). These traits are heritable, with Falconer's method showing a mean heritability (H 2 ) of 0.85 for theta-band traits, 0.76 for alpha-band traits, and 0.77 for beta-band traits across the temporal, frontal, and occipital cortex (Figure S4A).…”
Section: Heritability Of Neurophysiological Traitsmentioning
confidence: 99%
“…Novel neuromelanin-sensitive MRI measurements of SN and LC integrity hold promise for the non-invasive monitoring of the degeneration of dopaminergic and noradrenergic systems in PD 6,7 in relation to the respective hallmark motor and cognitive features of the disease 3,7 . A knowledge gap remains between these neurochemical observations and the well-documented alterations of rhythmic and arrhythmic neurophysiological activity in PD [8][9][10] , and whether any such associations relate to the cognitive and motor features of PD.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cortical alpha rhythms (8)(9)(10)(11)(12) are altered in PD, and, akin to the deterioration of the LC, relate to mild cognitive decline and PD dementia [11][12][13][14][15] . Whether the PD alterations of alpha activity are related to LC degeneration is an open question.…”
Section: Introductionmentioning
confidence: 99%